2017
DOI: 10.3390/recycling2020008
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Shredded Roof Membrane–Sand Mixture and Its Application as Retaining Wall Backfill under Static and Earthquake Loads

Abstract: About 20 billion square feet of Ethylene Propylene Diene Monomer (EPDM) rubber is installed on roofs in the United States and most of them will be reaching the end of their lifespan soon. The purpose of this study is to investigate potential reuses of this rubber in Civil Engineering projects rather than disposing it into landfills. First, laboratory tests were performed on various shredded rubber-sand mixtures to quantify the basic geotechnical engineering properties. The laboratory test results show that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The effect of rubber content on the friction angle has also been investigated. Livingston and Ravichandran [51] reported that the friction angle of the mixture increases with an increase in rubber content. In contrast, Lee et al [46] found that the friction angle of the mixture decreases with an increase in rubber content.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of rubber content on the friction angle has also been investigated. Livingston and Ravichandran [51] reported that the friction angle of the mixture increases with an increase in rubber content. In contrast, Lee et al [46] found that the friction angle of the mixture decreases with an increase in rubber content.…”
Section: Introductionmentioning
confidence: 99%
“…In most of the mentioned studies, it is concluded that up to a specific scrap rubber percentage, the higher the percentage of tire shreds or tire chips, the greater the shear strength [39]. While a few studies have concluded that the effects of granulated rubber on mixture behavior are similar to tire shreds and tire chips [40], many others have reported results showing the opposite [41]. In all types of scrap rubbers, however, by increasing aspect ratio and/or confining pressure, the shear strength has increased [41].…”
Section: Introductionmentioning
confidence: 99%
“…Granular filling materials are commonly placed inside confining structures for various engineering purposes; such applications include but are not limited to silos, trenches, mine stopes, and backfill retaining walls [1][2][3][4][5][6][7][8][9][10][11]. Upon placement, the fills settle downward due to self-weight, whereas the stiff confining walls tend to keep fills by limiting vertical displacements.…”
Section: Introductionmentioning
confidence: 99%